PERBANDINGAN SISTEM ECONOMIC ORDER QUANTITY DAN JUST IN TIME PADA PENGENDALIAN PERSEDIAAN BAHAN BAKU - Hayundra Maharani, Mayora; Kamal, Mustofa (Diponegoro Journal of Management, 2015)
As a publishing and printing company, the main raw material of CV Aneka Ilmu is the paper that used to print and to be made into a book or other products. In carrying out inventories of raw materials, the challenges faced by CV Aneka Ilmu is the storage of inventory control that the raw materials are not stored too big, that can caused the risks to damaged, obsolescences, and the loss of raw materials, as well as maintenance costs become higher and needs to be handle more. This study examines the raw material inventory control in the company, by comparing the two systems inventory. The purpose of this study was to compare the inventory system that has been carried out by CV Aneka Ilmu Semarang with two other inventory systems. The systems to be compared is Economic Order Quantity (EOQ) and  Just in Time (JIT), by comparing total inventory costs of each system to determine which of the systems that has the most efficient cost. The results indicate the best possibility for decision making in inventory system to CV Aneka Ilmu Semarang. The conclusion from this study that EOQ and JIT systems both more efficient in inventory cost compared to the company inventory sistem. But JIT system has cost efficiency level higher than EOQ system. In the inventory demand level of 1.550.530 rim, the company inventory sistem generates inventory cost by Rp 27.588.181,- compared to JIT that only has inventory cost by Rp 4.362.074.42,-, and can save costs about Rp 23.226.106,58,- or 84,19%. In this study also assumed there is tolerance (for damage, defect, and loss ) equal to 4% of the demand level was for 1.550.530 rim, become 1.612.551,2 rim. On the inventory demand level of 1.612.551,2 rim, both EOQ and JIT systems also more efficient in inventory cost compared to the company inventory system, but JIT system also more efficient compared to EOQ system. JIT system produce inventory cost amount Rp 4.471.288,079,- compared to company’s which is Rp 28.278.908,81,-. And with this JIT system can save up to Rp 23.807.620,73,- or 84,19% more efficient than company’s inventory cost.